Ilmu Fiqih dalam Perspektif Filsafat Ilmu - Khabibatun Nisa; M. Yunus Abu Bakar (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Fiqh is a branch of Islamic science that governs the legal aspects of human life. From the perspective of the philosophy of science, fiqh is not merely seen as a collection of laws but as a scientific discipline with ontological, epistemological, and axiological foundations. This study aims to analyze fiqh within the framework of the philosophy of science, focusing on how fiqh meets the criteria of science and its relevance to the needs of modern society. The research employs a qualitative approach with a literature review method, examining classical and contemporary works on fiqh and the philosophy of science. The findings reveal that fiqh possesses an ontological basis rooted in revelation and the sunnah, an epistemology that integrates reason with revelation, and an axiology emphasizing the benefit (maslahah) for humanity. The study concludes that fiqh not only fulfills the criteria of a scientific discipline but also plays a significant role in addressing contemporary challenges. The implications of this study highlight the necessity for a multidisciplinary approach in developing fiqh to ensure its relevance and applicability in modern times, particularly in addressing social, economic, and political issues.